2022
DOI: 10.3389/fonc.2022.944000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an integrated kinase-related prognostic gene signature associated with tumor immune microenvironment in human uterine corpus endometrial carcinoma

Abstract: In the worldwide, uterine corpus endometrial carcinoma (UCEC) is the sixth most common malignancy in women, and the number of women diagnosed is increasing. Kinase plays an important role in the occurrence and development of malignant tumors. However, the research about kinase in endometrial cancer is still unclear. Here, we first downloaded the gene expression data of 552 UCEC patients and 23 healthy endometrial tissues from The Cancer Genome Atlas (TCGA), obtained 538 kinase-related genes from the previous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…This suggests that TTK can be used as a potential biomarker to monitor disease and assess prognosis. In addition, TTK is related to immune infiltration and the immune microenvironment in various tumors [39][40][41], which also proves that the function of TTK may be related to immune function.…”
Section: Discussionmentioning
confidence: 70%
“…This suggests that TTK can be used as a potential biomarker to monitor disease and assess prognosis. In addition, TTK is related to immune infiltration and the immune microenvironment in various tumors [39][40][41], which also proves that the function of TTK may be related to immune function.…”
Section: Discussionmentioning
confidence: 70%
“…Univariate ( Wei et al, 2022 ) Cox regression model is a semi-parametric regression model. The model’s dependent variables are survival results and survival time.…”
Section: Methodsmentioning
confidence: 99%
“…Hsu et al have reported that the overexpression of FAM198B inhibits the invasion, proliferation, and tumorigenesis of lung adenocarcinoma cells, while the downregulation of FAM198B promotes the occurrence of malignant tumors (93). FAM198B was identified as a protective signature gene to predict the prognosis of uterine corpus endometrial carcinoma (94). FAM198B inhibits tumor invasion by downregulating the pERK/ MMP1 signaling pathway, while N-glycosylation enhances the FAM198B protein stability.…”
Section: Double-edged Sword: Fam198bmentioning
confidence: 99%